2020
DOI: 10.1021/acsami.0c04666
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Electrochemotherapy by Selenium-Doped Piezoelectric Biomaterials to Enhance Cancer Cell Apoptosis

Abstract: Cancer residues around the surgical site remain a significant cause of treatment failure with cancer recurrence. To prevent cancer recurrence and simultaneously repair surgery-caused defects, it is urgent to develop implantable biomaterials with anticancer ability and good biological activity. In this work, a functionalized implant is successfully fabricated by doping the effective anticancer element selenium (Se) into the potassium−sodium niobate piezoceramic, which realizes the wireless combination of electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Previous studies have demonstrated that functionalized nanomaterials could induce apoptosis of tumor cells in vitro or in vivo. For example, the Se nanosystem could stimulate apoptosis in human osteosarcoma cells and human breast cancer cells. , The mechanism underlying tumor therapy of Se was postulated to promote apoptosis of tumor cells. , Considering this, glucan Se system-induced cell death was investigated by flow cytometric analysis as shown in Figure . After treatment with 5.59 μg/mL glucan-SeNPs, 5.59 μg/mL glucan-RA-SeNPs, and 5.63 μg/mL RA for 24 h, the apoptotic cells in the treated samples were significantly increased from 5.37% to 20.40%, 42.02%, and 25.38%, respectively, compared with those in the control samples.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that functionalized nanomaterials could induce apoptosis of tumor cells in vitro or in vivo. For example, the Se nanosystem could stimulate apoptosis in human osteosarcoma cells and human breast cancer cells. , The mechanism underlying tumor therapy of Se was postulated to promote apoptosis of tumor cells. , Considering this, glucan Se system-induced cell death was investigated by flow cytometric analysis as shown in Figure . After treatment with 5.59 μg/mL glucan-SeNPs, 5.59 μg/mL glucan-RA-SeNPs, and 5.63 μg/mL RA for 24 h, the apoptotic cells in the treated samples were significantly increased from 5.37% to 20.40%, 42.02%, and 25.38%, respectively, compared with those in the control samples.…”
Section: Resultsmentioning
confidence: 99%
“…H&E staining results showed that the combined treatment group demonstrated obvious damage to tumor cells, such as increased intercellular space, extensive nuclear contraction and disappearance [ 58 ]. However, the local tumor tissue necrosis occurred in the P-BTO and P-BTO + LIPUS groups, which may be attributed to the surface electrostatic potential of nanoparticles inducing tumor cell apoptosis to a certain extent [ 59 ]. The expression of Ki-67 and the TUNEL assay also reflected the significantly inhibited tumor cell proliferation and the strongest apoptosis signal in the combined treatment group [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Se, which is an effective anticancer element, was doped into the KNN piezoceramic, realizing the wireless combination of electrotherapy and chemotherapy. [ 187 ]…”
Section: Advanced Designs Of Implants With Charge‐transfer Monitoring...mentioning
confidence: 99%
“…Similarly, Se, which is an effective anticancer element, was doped into the KNN piezoceramic, realizing the wireless combination of electrotherapy and chemotherapy. [187] The intensity and distribution of the constructed electric field are the key factors affecting the ion transfer between the material and the cells. The electric field intensity can be adjusted by regulating the polarization electric field intensity or changing the composition of the ferroelectric materials.…”
Section: Implants With Controlled Surface Potentialmentioning
confidence: 99%